Analysis of the Safety of the Krebet-Bululawang Highway Section in Review from the Completeness of Road Infrastructure Aspects - Primasworo, Rifky Aldila; Oktaviastuti, Blima; Nuha, Yusririn (JURUSAN TEKNIK SIPIL, 2025)
Road safety is a topic that is often raised, and is currently a world concern that not only affects transportation but also society. Therefore, it requires an analysis of road safety in terms of the completeness of road infrastructure to meet the standard value of the Indonesian Road Capacity Guideline. and the National General Plan for Road Traffic and Transportation Safety (RUNKLL). The purpose of the study was to determine the accident-prone points on the Krebet-Bululawang highway, Malang Regency. and provide handling efforts related to the results of the Krebet Highway Safety Analysis in Review from the Completeness of Road Infrastructure Aspects. In this study, what is calculated is the Z-score Technical Analysis of accident-prone areas (Black sites), the Cusum Technique of accident-prone points (Black Spot). Based on the results of accident characteristic data processing, the location of accident-prone points (black spots) that have the largest custom value on Jalan Krebet is identified as accident-prone points in segments 1 and segment 3 as the cause of having the largest custom values, namely 7,200 and 5,250. Based on the accident data, the accident z-score values for each segment were obtained based on the total number of accident incidents during the period 2018 - 2022 with 2 road segments with the highest scores, namely segments 1 and 3 where the number of accident victims was 11 accident victims and the highest z-core value was 2.012 in segment 1 and segment 3 0.224 Identify characteristics that are deeper and more detailed, this is based on the results of analysis of accident z-score values that appear 2 priority road segments and aim in efforts to handle accident-prone segment location points that have been identified and determined previously. At this stage, the most important technical problems in road traffic safety will be described as Proposed Handling for accident-prone areas (black sites) and accident-prone points (back spots) that need to be installed warning signs for dangerous areas where accidents often occur. Usually the placement of these traffic signs is at least 50 meters before areas where accidents often occur according to the standard of RI transportation regulations No PM 13 2014 concerning traffic signs.